2019
DOI: 10.1017/jfm.2019.435
|View full text |Cite
|
Sign up to set email alerts
|

Control of oblique-type breakdown in a supersonic boundary layer employing streaks

Abstract: The effectiveness of streak modes in controlling the oblique-type breakdown in a supersonic boundary-layer at Mach 2.0 is investigated using direct numerical simulations. Investigations in the literature have shown the effectiveness of streak modes in delaying the onset of transition dominated by two-dimensional waves, but in oblique breakdown, three-dimensional waves and a strong streak mode dominate the transition process. Paredes et al. (J. Fluid Mech., vol. 831, 2017, pp. 524–553) discussed the possible st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…At the further downstream locations, the disturbance amplitude begins to increase close to the wall, leading to the higher slope of the skin friction curve as observed in figure 8(a). Recent studies have shown that under certain set of parameters, stationary streaks can stabilize oblique first-mode waves in supersonic boundary-layer flows (Paredes et al 2017;Sharma et al 2019) and Mack-mode waves in hypersonic boundary-layer flows (Paredes, Choudhari & Li 2019a). However, at large enough amplitudes, the same streaks are able to induce transition via streak instabilities (Paredes et al 2017(Paredes et al , 2019a.…”
Section: Nonlinear Evolution Of Non-modal Oblique Travelling Disturbamentioning
confidence: 99%
“…At the further downstream locations, the disturbance amplitude begins to increase close to the wall, leading to the higher slope of the skin friction curve as observed in figure 8(a). Recent studies have shown that under certain set of parameters, stationary streaks can stabilize oblique first-mode waves in supersonic boundary-layer flows (Paredes et al 2017;Sharma et al 2019) and Mack-mode waves in hypersonic boundary-layer flows (Paredes, Choudhari & Li 2019a). However, at large enough amplitudes, the same streaks are able to induce transition via streak instabilities (Paredes et al 2017(Paredes et al , 2019a.…”
Section: Nonlinear Evolution Of Non-modal Oblique Travelling Disturbamentioning
confidence: 99%
“…Building on the previous results the present DNS study is aimed at providing clear evidence of the robustness of the control technique employing steady streaks at a supersonic Mach number. The paper is organized as follows: first, we give details about the computational set-up used and its validation by comparing with results by Fezer & Kloker (2000) and Sharma et al (2019), where different DNS codes have been used. Following this, the control streaks are applied to a boundary layer perturbed by fundamental and subharmonic disturbances, simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Fluidic control has proven to be a very versatile control mean that, for example, has been successfully employed to manage the transition process in compressible flows (see Refs. [11,12]). These methods require a close consideration of the complete problem.…”
Section: Optimization Of a Fluidic Vortex Generator's Control In A Transonic Channel Flowmentioning
confidence: 99%